Pengembangan Alat Ukur Citra Merek Telepon Seluler - Purnomolugi Ursila Nilamsari; Laurentius Purbo Christianto; Agatha Angel (Suksma: Jurnal Psikologi Universitas Sanata Dharma, 2022)
Measurement of mobile phone brand image is important. In the context of Indonesian consumers, it is also important to measure the brand image of cellular phones to encourage product innovation that contains the indigenous values of the Indonesian nation and can support sustainable growth in the industrial era 4.0. For this measurement, it is necessary to measure the brand image of a cellular phone. This study aims to develop a measuring instrument for Cellular Phone Brand Image that can be used by Indonesian consumers. The brand image model by Aaker (1997) and the brand value proposed by Zhang (2011) became the basis for making instrument items. The instrument trial involved 300 participants aged 18-40 years. The analysis of exploratory factor analysis resulted in 27 items grouped into 3 factors, namely functional benefits, brand associations, and personality characteristics. These three factors showed that brand characteristics and personal considerations have the same role in building a cellular phone brand image Keywords: Brand Image Scale,  Cellular Phone